Synthesis and Supramolecular Structure of 4,4’,6,6’-Tetrachloro-2,2’-[(decane-1,10-diyldioxy)bis(nitrilomethylidyne)]diphenol - Dong, Wen-Kui; Li, Xiang; Wu, Jun-Jiang; Zhang, Yang; Tang, Xiao-Lu (Asian Journal of Chemistry, 2013)
A new salen-type bisoxime compound, 4,4',6,6'-tetrachloro-2,2'-[(decane-1,10-diyldioxy)bis(nitrilomethylidyne)]diphenol, has been synthesized and characterized structurally. In each molecule, there is a trans configuration with respect to the methylidene unit. The two phenyl rings in each molecule are paralle to each other, with a perpendicular interplanar spacing of ca. 6.583(2) Å. In the crystal structure, each molecule links other two molecules into finite 2D supramolecular structure by two pairs of intermolecular C10-H10···Cl2 hydrogen bonds.